HIV-1 Integrates Widely throughout the Genome of the Human Blood Fluke Schistosoma mansoni. - Sutas Suttiprapa; Gabriel Rinaldi; Isheng J Tsai; Victoria H Mann; Larisa Dubrovsky; Hong-Bin Yan; Nancy Holroyd; Thomas Huckvale; Caroline Durrant; Anna V Protasio; Tatiana Pushkarsky; Sergey Iordanskiy; et al. (PLoS Pathogens)
Schistosomiasis is the most important helminthic disease of humanity in terms of morbidity and mortality. Facile manipulation of schistosomes using lentiviruses would enable advances in functional genomics in these and related neglected tropical diseases pathogens including tapeworms, and including their non-dividing cells. Such approaches have hitherto been unavailable. Blood stream forms of the human blood fluke, Schistosoma mansoni, the causative agent of the hepatointestinal schistosomiasis, were infected with the human HIV-1 isolate NL4-3 pseudotyped with vesicular stomatitis virus glycoprotein. The appearance of strong stop and positive strand cDNAs indicated that virions fused to schistosome cells, the nucleocapsid internalized and the RNA genome reverse transcribed. Anchored PCR analysis, sequencing HIV-1-specific anchored Illumina libraries and Whole Genome Sequencing (WGS) of schistosomes confirmed chromosomal integration; >8,000 integrations were mapped, distributed throughout the eight pairs of chromosomes including the sex chromosomes. The rate of integrations in the genome exceeded five per 1,000 kb and HIV-1 integrated into protein-encoding loci and elsewhere with integration bias dissimilar to that of human T cells. We estimated ~ 2,100 integrations per schistosomulum based on WGS, i.e. about two or three events per cell, comparable to integration rates in human cells. Accomplishment in schistosomes of post-entry processes essential for HIV-1replication, including integrase-catalyzed integration, was remarkable given the phylogenetic distance between schistosomes and primates, the natural hosts of the genus Lentivirus. These enigmatic findings revealed that HIV-1 was active within cells of S. mansoni, and provided the first demonstration that HIV-1 can integrate into the genome of an invertebrate.